Influence of inter‐parental conflict on adolescent delinquency via school connectedness: Is impulsivity a vulnerability or plasticity factor?. (29th July 2016) - Liu, Sha; Yu, Chengfu; Zhen, Shuangju; Zhang, Wei; Su, Ping; Xu, Yang
ABSTRACT: This study examined the mediating effect of school connectedness on the relationship between inter‐parental conflict and adolescent delinquency, and impulsivity's moderation of the conditional effect of school connectedness. In total, 1407 Chinese students (mean age = 12.74 years, SD  = 0.57) from 4 middle schools completed anonymous questionnaires regarding inter‐parental conflict, impulsivity, school connectedness, and delinquency. Path analysis revealed school connectedness was a mediator in the relationship between inter‐parental conflict and adolescent delinquency. Furthermore, impulsivity moderated the indirect effect of school connectedness in the relationship between inter‐parental conflict and adolescent delinquency. A simple slope plot, together with a proportion affected (PA) index, indicated that impulsivity functioned more as a plasticity, rather than a vulnerability, factor in school connectedness. When school connectedness was low, high impulsivity was associated with more delinquent behaviors; however, when it was high, high impulsivity was associated with fewer delinquent behaviors.